2022
DOI: 10.1038/s41419-022-04680-5
|View full text |Cite
|
Sign up to set email alerts
|

Toll-like receptor 3 activation promotes joint degeneration in osteoarthritis

Abstract: Osteoarthritis (OA) is characterized by cartilage degradation that is induced by inflammation. Sterile inflammation can be caused by damage-associated molecular patterns that are released by chondrocytes and activate pattern recognition receptors. We evaluate the role of toll-like receptor-3-activating RNA in the pathogenesis of OA. Toll-like receptor 3 (TLR3) was detected by semiquantitative reverse transcriptase PCR, western blotting and microscopy. Rhodamine-labelled poly(I:C) was used to image uptake in ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 44 publications
0
7
0
Order By: Relevance
“…Instead, these TLRs are only activated in the event that extracellular DNA or RNA from damaged or dead bystander cells has been endocytosed and the nucleic-acid-containing endosome fuses with an acidified endosome containing the TLRs [ 78 ]. Indeed, there are several reports in the literature where extracellular mRNA or mitochondrial RNA derived from damaged cells has been engulfed by neighboring cells, resulting in TLR3 activation and sterile inflammation [ 63 , 79 , 80 ]. Highlighting a route for entry for nucleic acids, Bertheloot et al showed that RNA released from damaged cells can be detected by the receptor for advanced glycation end products (RAGE) to elicit their internalization and activate TLR7 and TLR8 [ 81 ].…”
Section: Tlr Activation In the Kidneymentioning
confidence: 99%
“…Instead, these TLRs are only activated in the event that extracellular DNA or RNA from damaged or dead bystander cells has been endocytosed and the nucleic-acid-containing endosome fuses with an acidified endosome containing the TLRs [ 78 ]. Indeed, there are several reports in the literature where extracellular mRNA or mitochondrial RNA derived from damaged cells has been engulfed by neighboring cells, resulting in TLR3 activation and sterile inflammation [ 63 , 79 , 80 ]. Highlighting a route for entry for nucleic acids, Bertheloot et al showed that RNA released from damaged cells can be detected by the receptor for advanced glycation end products (RAGE) to elicit their internalization and activate TLR7 and TLR8 [ 81 ].…”
Section: Tlr Activation In the Kidneymentioning
confidence: 99%
“…In vitro, it was revealed that TLR-3 is upregulated in chondrocytes of OA cartilage and reacts to apoptotic chondrocytes. The TLR-3 knockout mice were protected from OA-like cartilage breakdown [ 177 ]. It is also worth mentioning, that satellite glial cells of the dorsal root ganglia (DRG) express many TLRs.…”
Section: Pathological Changes In Oa-affected Joint Tissuesmentioning
confidence: 99%
“…Afterwards, the fluorescence images were analyzed by cell counting using ImageJ for Windows. TUNEL-and DAPI-positive cells were put into relation ((TUNEL positive cells/total number of cells) *100) [36].…”
Section: Cell Death Detectionmentioning
confidence: 99%